Screening soybean germplasm for aluminium tolerance using cluster analysis - Spehar, Carlos Roberto (Pesquisa Agropecuaria Brasileira, 1994)
Principal component and cluster analyses were carried out to assess diversity on soybean germplasm selected to cultivation in the Brazilian Savannas (Cerrados). The results indicated that aluminium tolerance was attained in the breeding material which showed variability when tested in the high-Al environment. The ample tolerance may have been a consequence of breeding and selecting soybeans in improved soils that were still Al-rich in deeper layers, although the varieties were homogeneous for agronomic characters, as shown by the analysis of data from the low-Al environment. This method can be successfully employed in genetic studies and in breeding programmes for crop improvement when parents of different clusters are chosen for crossing.